Hermeneutika Al-Qur’an: Memburu Pesan Manusiawi dalam Al-Qur’an - Aksin Wijaya (Universitas Islam Negeri Mataram, 2011)
The Holy Qur’an, theoretically, is God’s holy book which is for human being. But, Qur’anic exegesis domination, which extends for centuries, gets the exegesis to be covered by theological concepts. The Holy Qur’an forgets about its dimension of humanity, and just focuses on its theological dimension. Exegesis discourse revolves around moslem communities so far tells much more about God than about human being; it cares much more of God the Almighty than of human being, the weak. It, therefore, needs theoretical interpretation that is able to explore humanity dimension of Qur’an without forgetting about its God dimension, in order that holy Qur’an as a main source of Islam could care of human being. It is a holy book from Allah to Human being.